Cinobufagin exerts anti-proliferative and pro-apoptotic effects through the modulation ROS-mediated MAPKs signaling pathway. (June 2015) - Baek, Seung Ho; Kim, Chulwon; Lee, Jong Hyun; Nam, Dongwoo; Lee, Junhee; Lee, Seok-Geun; Chung, Won-Seok; Jang, Hyeung-Jin; Kim, Sung-Hoon; Ahn, Kwang Seok
Abstract Cinobufagin (CBG) is a cardiotoxic bufanolide steroid secreted by the skin and parotid venom glands of the Asiatic toad Bufo bufo gargarizans (called Chan-Su). Although CBG is known to exhibit anti-cancer activities, very little is known about its potential mechanism(s) of action. In this study, we investigated whether CBG mediates its effect through the modulation of the mitogen-activated protein kinases (MAPKs) signaling pathway in human multiple myeloma (MM) U266 cells. We found that CBG caused the significant activation of ERK, JNK and p38 MAPK in U266 cells. CBG showed much higher cytotoxicity against U266 cells as compared to peripheral blood mononuclear cells (PBMC). Induction of CBG increased reactive oxygen species (ROS) generation from mitochondria, which is associated with the induction of apoptosis as characterized by increased sub-G1 DNA contents of cell cycle, positive Annexin V binding, activation of caspase-3 and cleavage of PARP. Inhibition of ROS generation by N-acetyl-l-cysteine (NAC) significantly prevented CBG-induced ERK, JNK and p38 MAPK activation and apoptosis. CBG also down-regulated the expression of various downstream gene products that mediate cell proliferation, survival, angiogenesis and metastasis. Interestingly, ERK, JNK and p38MAPK pharmacological inhibitors blocked CBG-induced MAPKs activation and ERK inhibitor (PD98059) also prevented the CBG-induced caspase-3 activation and PARP cleavage in U266 cells. Taken together, these findings suggest that CBG can act as a potent anticancer agent against MM and possibly exerts its effects through the ROS-mediated activation of ERK, JNK and p38 MAPK leading to the activation of caspase-3 in U266 cells.